A Naturally Occurring Feline Model of Head and Neck Squamous Cell Carcinoma. (16th July 2013) - Wypij, Jackie M.
Abstract : Despite advances in understanding cancer at the molecular level, timely and effective translation to clinical application of novel therapeutics in human cancer patients is lacking. Cancer drug failure is often a result of toxicity or inefficacy not predicted by preclinical models, emphasizing the need for alternative animal tumor models with improved biologic relevancy. Companion animals (dogs and cats) provide an opportunity to capitalize on an underutilized and biologically relevant translational research model which allows spontaneous disease modeling of human cancer. Head and neck squamous cell carcinoma (HNSCC) is a common cancer with a poor prognosis and limited clinical advancements in recent years. One potential novel spontaneous animal tumor model is feline oral squamous cell carcinoma (FOSCC). FOSCC and HNSCC share similar etiopathogenesis (tobacco and papillomavirus exposure) and molecular markers (EGFR, VEGF, and p53). Both human and feline SCCs share similar tumor biology, clinical outcome, treatment, and prognosis. Future clinical trials utilizing FOSCC as a tumor model may facilitate translation of preclinical cancer research for human cancer patients.